Discovery of tetrahydro γ-carboline based novel glucose uptake agent for the treatment of diabetes and Alzheimer's diseases - Voggu, Ramakrishna (2024)
The emergence of diabetes mellitus (DM), one of the prevalent metabolic disorders, has increased at alarming rates around the globe in the past few decades. The early discovery of insulin paved the way for the broadened non-invasive anti-hyperglycemic drug therapies to manage and treat diabetes. Recently, insulin resistance in brain tissues has been considered a new hallmark of disease progression, leading to neurodegeneration. Tetrahydro γ-carbolines are privileged scaffolds with various activities against obesity, cancer, and central nervous system (CNS) diseases. The failure of Latrepirdine in clinical phase trials as anti-AD, prompted us to explore further the γ-Carboline derivatives with anti-diabetic activity. To address this, we have leveraged our expertise in drug design to develop tetrahydro γ-carboline derivatives and studied their effect on glucose uptake. All the compounds exhibited low cytotoxicity towards the mammalian cell line 3T3-L1. Next, we screened the 10 derivatives to identify the novel anti-diabetic activities using a fluorescent glucose analog 2-NBDG (2-(N-(7-nitrobenz-2-oxa-1, 3-diazol-4-yl)-2-deoxy-D-glucose) based on a glucose-uptake assay in differentiated 3T3-L1 adipocytes. Compound 11a has significantly increased glucose uptake at 100 µM compared to rH-Insulin. The dose optimization (1 nM-100 nM) of lead compounds for 2-NBDG-glucose uptake clearly indicated that 11a is superior compared to Insulin. The 11a is the close analog of Latrepirdine, an anti-histamine drug, reported for Alzheimer disease (AD). Further, to understand its anti-AD potential we carried out in silico docking studies with its probable targets, Acetylcholinesterase (AChE), 5-hydroxytryptamine (5HT6) receptor, Butyrylcholinesterase (BChE), and N-methyl-D-aspartate (NMDA) receptor. The docking studies revealed that 11a had stronger binding to these targets than Latrepirdine, correlating with the glucose uptake assay. Thus, 11a is a potential lead disease-modifying agent and could be considered for the management and treatment of type 2 DM and AD.